Job Stress Level as Perceived by Staffs in the Government Sector Case Study: MARA Kuching, Sarawak - Bilal, Kamalludin; Ali, Siti Noraza; Abg Naim, Abg Sulaiman; Ali, Nurlaila; Ashmat, Ismail (International Journal of Management Excellence (ISSN: 2292-1648), 2014)
Stress is a reaction to excessive pressure or harassment at work. It is a physical, mental, or emotional response to events that cause bodily or mental tension. People in stress conditions may find it is hard to concentrate on any task and cannot be relied on to do their share. Some employers assume that stressful working conditions turns up the pressure on workers. A set aside health concerns; it will affect the productivity and profitability in today’s economy. This paper purposely to identify the level of job stress among government staffs. This study was carried out using a set of questionnaire and survey method. The questionnaire was distributed to 150 staffs of Majlis Amanah Rakyat (MARA) Kuching as representative of government sector and was analysed using SPSS version 19. The study had shown that most of the respondents were moderately stressful. It is very important that the organisations understands the needs of its employees and provide what is best for the employees.